Immune reconstitution in HIV-1 infected patients treated for two years with highly active antiretroviral therapy - Almeida, Ricardo Augusto Monteiro de Barros [UNESP]; Souza, L. R. [UNESP]; Calvi, Sueli Aparecida [UNESP]; Ikoma, M. R V; Silva, V. A.; Curi, P. R. [UNESP]; Meira, D. A. [UNESP] (FapUNIFESP (SciELO), 2006)
The aim of this paper was to evaluate the immune reconstitution of HIV-1 patients subjected to highly active antiretroviral therapy (HAART) for two years or more according to CD 45RA and CD 45RO cell count; determination of IL-2, IFN-γ, IL-4, IL-10 and TNF-α serum levels; CD 4 + T and CD 8 + T lymphocyte count; and plasma viral load (VL) determination. For this purpose, a cross sectional study was carried out in the Tropical Diseases Area, Botucatu School of Medicine, São Paulo State University, UNESP, Botucatu, São Paulo, Brazil. Between June 2001 and April 2002, 37 HIV-1 infected patients were evaluated, 13 with treatment indication but untreated (G1), 9 subjected to HAART for 5-7 months (G2), and 15 treated for two years or more (G3); both treated groups used medication regularly and without failure. Forty-nine normal individuals were studied as controls (GC-1 and GC-2). There was a tendency (p<0.10) for the predominance of two nucleoside reverse transcriptase inhibitors (NRTI) associated with one non-nucleoside reverse transcriptase inhibitor (NNRTI) regimen in G2; and two NRTI associated with a protease inhibitor (PI) in G3. Statistical differences between groups were seen for CD 45RA (G1<[G3=GC-2]; p<0.05) and CD 45RO (G1<GC-2<G3; p<0.01) cells, and CD 4 + T lymphocyte count (G1<G3; G2-intermediate; p<0.05), VL determination (G1>[G2=G3]; p<0.001), TNF-α serum determination ([G1>G3; G2=intermediate]>GC-1; p<0.001), IL-2 (G1<[G2=G3=GC-1]; p<0.01), IFN-γ ([G1=GC-1]>[GC-2=G3]; p<0.001), IL-4 and IL-10 ([G1=G2=G3]>GC-1; p<0.001), serum cytokine profiles, with a higher proportion of subtype 2 in G1 and mature subtype 0 in G2 and G3 (p<0.005). There was no statistical difference for CD 8 + T lymphocyte counts (G1=G2=G3; p<0.50). Consistency was seen between positive correlations of profile 1 definer cytokines (IL-2 and IFN-γ), CD 45RA and CD 45RO cells, and CD 4 + T lymphocyte counts and between positive correlations of profile 2 definer cytokines (IL-4 and IL-10) with TNF-α, and VL. The negative correlations were also consistent as they expressed the inverse of the positives. The variables with the highest number of correlations were IL-2, IFN-γ, and VL, followed by CD 45RA and CD 45RO cells, and IL-10. The variables with the lowest number of correlations were CD 4 + T and CD 8 + T lymphocytes. The results express the partial but important immune reconstitution in HIV-1 infected individuals with the interference of HAART and the importance of cytokines especially IL-2 and IFN-γ, and CD 45RA and CD 45RO cells as surrogate markers of this reconstitution.
Keywords: Antiretroviral; CD 45RA; Cd 45RO; Cytokines; HAART; HIV; Immune reconstitution; Human immunodeficiency virus; Human immunodeficiency virus 1